Biogeography and genetic consequences of anagenetic speciation of Rhaphithamnus venustus (Verbenaceae) in the Juan Fernández archipelago, Chile: insights from AFLP and SSR markers. Issue 3 (16th September 2016) - López‐sepúlveda, Patricio; Takayama, Koji; Crawford, Daniel J.; Greimler, Josef; Peñailillo, Patricio; Baeza, Marcelo; Ruiz, Eduardo; Kohl, Gudrun; Tremetsberger, Karin; Gatica, Alejandro; Letelier, Luis; Novoa, Patricio; et al.
Abstract : The genus R haphithamnus (Verbenaceae) consists of two species, one in South America and another endemic to the Juan Fernández archipelago, Chile. The genus represents an example of anagenetic speciation in which the island populations have diverged from their colonizing ancestors to the point where they are recognized as a distinct species. The island species R haphithamnus venustus differs from the continental R . spinosus primarily by floral traits associated with adaptation to hummingbird pollination. Two molecular markers, amplified fragment length polymorphisms (AFLPs) and microsatellites, were used to estimate divergence between the continental and insular species, and to compare diversity in the two species. The comparable or greater diversity in the insular species observed in some diversity indices of AFLPs would support the hypothesis that during the course of anagenetic speciation it has recovered from any reduction of genetic diversity associated with colonization of the archipelago. This pattern of comparable or higher diversity in insular species is seen with other instances of anagenetic speciation in the Juan Fernández archipelago. By contrast, the lower genetic diversity in the insular R . venustus found in microsatellites is likely to be the result of a founder effect from the original colonization of the archipelago; prior molecular studies suggest recent colonization of the Juan Fernández archipelago by R haphithamnus . The seeming non‐concordance between the present results and the widely accepted biogeography of R haphithamnus inferred from other data is discussed and an explanation is presented. Abstract : The genus R haphithamnus (Verbenaceae) consists of two species, one in South America and another endemic to the Juan Fernández archipelago, Chile, which represents an example of anagenetic speciation in which the island populations have diverged from their colonizing ancestors to the point where they are recognized as a distinct species. Two molecular markers, AFLPs and microsatellites, were used to estimate divergence between the continental and insular species, and to compare diversity in the two species. The comparable or greater diversity in the insular species observed in some diversity indices of AFLPs, but the lower genetic diversity in the insular R . venustus found in microsatellites.